Sportivnyj management v Evropy - Zolotov, M. I.; Kuzmiceva, E. B. (Teorija i Praktika fiziceskoj Kul'tury, 2004)
For the recent years growth of free economic market of sports is marked: the occurrence of new consumers, growth of the industry of sports. The urgency of questions of management in sports was caused by the growth of volume of mass information and especially satellite TV, the exponential increase of the number of TV translations of the largest sports events, amplification of political value of sports and its role in the world economy and trade. Nowadays sports managers work in conditions of new administrative structures, with the innovational technologies, new ideas and new values. From the beginning of the 80th educational projects started to operate, and since 1991 the network of the educational management centres in higher educational institutions appeared.